Odpowiedź :
7)
a) [tex]\frac{3}{5} *\frac{1}{10} -\frac{252}{25}[/tex] = [tex]\frac{3}{50} -\frac{252}{25} = -\frac{501}{50} = -10\frac{1}{50}[/tex]
b) [tex]5+(-\frac{19}{6} )*\frac{3}{5} = 5-\frac{19}{2} *\frac{1}{5} =5-\frac{19}{10}=\frac{31}{10} =3\frac{1}{10}[/tex]
c) [tex]\frac{23}{4} :(-\frac{1}{4} )+25=-\frac{23}{4} *4+25=2[/tex]
d) [tex]\frac{7}{3} -\frac{7}{2} *\frac{7}{10} =\frac{7}{3} -\frac{49}{20} =-\frac{7}{60}[/tex]
8)
a) [tex]\frac{16}{3} -\frac{29}{4} -\frac{3}{4}[/tex] [tex]=\frac{16}{3}+\frac{-32}{4} =\frac{16}{3} -8=\frac{16-24}{3} =-\frac{8}{3}[/tex]
b) [tex]\frac{11}{6} -\frac{13}{12} -\frac{1}{2} *\frac{3}{2} =\frac{11}{6} -\frac{13}{12} -\frac{3}{4}=0[/tex]
c) [tex]9+2^{3} *\frac{1}{2^{3} } =10[/tex]
d) [tex](-\frac{4}{5} ):(-8,6)[/tex] = [tex](-\frac{4}{5} ):(-\frac{43}{5} )=\frac{4}{5} *\frac{5}{43} =\frac{4}{43}[/tex]